The Old Yellow Enzyme OfrA Fosters Staphylococcus aureus Survival via Affecting Thiol-Dependent Redox Homeostasis - Ibrahim, Eslam S.; Ohlsen, Knut (Frontiers in Microbiology, 2022)
Old yellow enzymes (OYEs) are widely found in the bacterial, fungal, and plant kingdoms but absent in humans and have been used as biocatalysts for decades. However, OYEs physiological function in bacterial stress response and infection situations remained enigmatic. As a pathogen, the gram-positive bacterium Staphylococcus aureus adapts to numerous stress conditions during pathogenesis. Here we show that in S. aureus genome, two paralogous genes (ofrA and ofrB) encode for two OYEs. We conducted bioinformatic analysis and found that ofrA is conserved among all publicly available representative staphylococcal genomes and some Firmicutes. Expression of ofrA is induced by electrophilic, oxidative, and hypochlorite stress in S. aureus. Furthermore, ofrA contributes to S. aureus survival against reactive electrophilic, oxygen, and chlorine species (RES, ROS, RCS) via thiol-dependent redox homeostasis. At the host-pathogen interface, S. aureusΔofrA has defective survival in macrophages and whole human blood and decreased staphyloxanthin production. Overall, our results shed the light onto a novel stress response strategy in the important human pathogen S. aureus.